Models for Recognizing Indigenous Land Rights in Latin America - Roldán Ortega, Roque (World Bank, Washington, DC, 2014)
This paper represents an important dimension in filling Latin America history's gaps through the lens of land rights. The continent was populated by many nations, functioned in harmony with nature, had a variety of cultures and languages, and, developed many different socio-economic systems (nationally and locally). These nations were sovereign and recognized from Alaska to Patagonia. Indeed, among all of them, we know they had very advanced, and well established institutional arrangements and organizations (formal and informal), created and nurtured with the view to respond to the needs, and challenges of the time. With a variety of forms of governance, these societies did assign rights, and responsibilities to the different actors, and groups in order to maintain an acceptable level of social cohesion, to establish important political consensus. As the political systems of some countries are now becoming more democratic to listening, and embracing the views of minorities, issues of land rights have clearly surfaced. Issues of sovereignty, customary law and, simply, of traditional norms-from the national to the household levels-are being put on the table of what is clearly a complex social dialogue. The paper is an excellent source of basic information, sharing an easy and practical understanding about land tenure/titling, as discussed above. In addition, the paper represents a genuine attempt to: a) recognize the existence of these complex land rights and land titling systems across Latin America; b) study the content at the country level, so that international experiences/comparisons may spark a move towards policy coherence and legislation; and, c) demonstrate that land is not only a physical asset with some economic and financial value, but an intrinsic dimension, and part of peoples lives and belief systems. There is also a human rights dimension to all of the above. And it is essential to understand this human rights dimension of land rights, not just as a legal obligation, but as a key element of economic and social development.